Cystic Glioblastoma: A Mimicker of Infection? A Case Report and Literature Review. (17th January 2023) - Thirugnanasambandam, Ram Prakash; Silva, Gaudy Massiel Vanegas; Wu, Alexander H.; Kim, Charles J.; Cimpeanu, Emanuela; Minkowitz, Jeremy; Shao, Charles Yanping; Chiu, Edwin
Abstract : Glioblastoma multiforme (GBM) is the most frequent malignant and aggressive type of glioma. Most cases of GBM present as a single solitary solid tumor; however, there are rare instances in which it may present as a cystic lesion. Here, we report an even rarer case of GBM presenting as bilateral multicystic lesions, mimicking infectious etiology. Our case highlights the importance of identifying clinical features of cystic GBM to ensure early diagnosis and treatment. A literature review was conducted in PubMed, looking at the common characteristics and treatment options for cystic GBM.